Time-saver standards for architectural design : technical data for professional practice - Watson, Donald, 1937-; Crosbie, Michael J. (New York : McGraw-Hill, 2005)
Accompanying CD-ROM contains ... "additional, still-current chapters from the Seventh edition." -- p. [4] of cover.
Includes bibliographical references and index.
Keywords: Building -- Handbooks, manuals, etc; Standards, Engineering -- Handbooks, manuals, etc; Architectural design -- Handbooks, manuals, etc